Magnetically induced transparency of a quantum metamaterial composed of twin flux qubits - K. V. Shulga; E. Il’ichev; M. V. Fistul; I. S. Besedin; S. Butz; O. V. Astafiev; U. Hübner; A. V. Ustinov (Nature Communications, 2018)
Here, the authors demonstrate an array of superconducting qubits embedded into a microwave transmission line. They show that the transmission through the metamaterial periodically depends on externally applied magnetic field and suppression of the transmission is achieved through field-induced transitions.